Pemanfaatan Aplikasi Mathway: Systematic Literature Review - Milda Zohra; Yahfizham Yahfizham (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze meta data related to the use of the Mathway application by looking at research objectives that relate to the use of the Mathway application. This research uses the SLR (Systematic Literature Review) method. This systematic review identified 8 articles through the Google Scholar database published in 2018-2023. Data collection used the PRISMA procedure. The results of this research show that there are 3 research objectives related to the use of applications in mathematics learning, namely, 1) To find out how important the influence of technology is on mathematics learning for educators and students, 2) To find out how useful an application is in mathematics learning for educators and students, 2) To find out how useful an application is in mathematics learning for educators and students, and 3) To determine learning outcomes based on student interest and learning motivation.